130 UNUSUAL PRESENTATION OF DIFFUSE LARGE B-CELL LYMPHOMA. Issue 1 (1st January 2007) - Persing, B.; Herrin, V.; Elkins, S.; Files, J.; Bigelow, C.
Abstract : Introduction: Diffuse large B-cell lymphoma (DLBCL) comprises 31% of non-Hodgkin's lymphomas (NHL), making DLBCL the most common form of NHL. DLBCL typically presents as a rapidly expanding abdominal or neck mass but can also present as extranodal disease. This case is an example of an unusual site for extranodal presentation of DLBCL. Case Presentation: A 39-year-old white female presented to an outside facility with a breast mass that was rapidly growing. She stated that the mass had been stable and present for the previous 5 years with just a minimal increase in size. The mass measured approximately 9.0 × 3.6 × 7.9 cm. Following several core needle biopsies and a right total mastectomy with conflicting pathology, removal of a mass in the surgical incision site yielded the diagnosis of DLBCL. The patient had a normal LDH and staging revealed disease confined to the breast. The patient was subsequently started on cyclophosphamide, vincristine, Adriamycin, prednisone, and rituximab (CHOP-R.). Discussion: DLBCL is the most common form of NHL. Primary extranodal disease arising from the breast has been documented but remains an uncommon site of initial disease. A plausible explanation of the initial benign nature of this patient's mass is an initial low-grade lymphoma with subsequent conversion to a high-grade lymphoma. At present, there is a lack of randomized trials for the treatment of primary breast lymphoma. Conclusion: Diffuse large B-cell lymphoma can present in unusual manners and arise from a previously benign-appearing lesion. Difficulty obtaining a diagnosis can lead to a delay in treatment and potentially more advanced stage of disease at the time of initiation of treatment. An appropriate index of suspicion and thorough evaluation may expedite diagnosis and prevent a delay in treatment.